DEVELOPING SENIOR HIGH SCHOOL STUDENTS WRITING SKILL THROUGH LEARNER-BASED TEACHING - Nurhasanah, Amalia (Reflective, 2012)
Teaching writing in English as a foreign language to Indonesian students is truly essential. Through writing, students can express their feeling, idea, and also their knowledge in the visual demonstration. Infact, writing interest of the senior high school students in Indonesia is low. That problem might be caused by many reasons from both the teacher and students aspects. This paper is proposing one technique in teaching text writing that is Learner-Based Teaching [a technique in teaching English which has main principle that all class activities can be done using information that the learners themselves bring to the class]. Analyzing the examples of Learner-Based Teaching classroom activities we can conclude that Learner-Based Teaching is advantageous in increasing the studentsâ writing ability not only for the students but also for the teacher in term of motivation, effectiveness of Teaching-Learning activities, and relations among all.